Infoinclusão: discursos, representações e práticas de subjetivação do professor web 2.0 na cibermídia - Pires, Alcione Rodrigues (2010)
Digital inclusion can be understood as the technology used to create an effective social inclusion and, by providing equipment which will be used as instruments of social mobilization and of education, become a way of people being socially and digitally included.To be digitally included means to have access and knowledge to make use of information and communication technologies. On the internet, we find many actions to make that effective, for instance, governmental and also private educational portals, specialized websites, blogs, forums and a few others technological devices. The discursive practices found in those virtual spaces about the teacher and the new technologies show an unprepared educator when dealing with internet issues and, more specifically, with Web 2.0. In the first generation of commercial Internet the user only played a spectator role on these pages, with no access or authorization to modify any content, which characterized the Web 1.0 period. Nowadays, this one way street is over, and the web users can put their own contents online: it is the Web 2.0 phase. Still, the term “Web 2.0” is not clear for everyone and it seems too soon to talk about Web 3.0 it. Our objective with this paper is to identify the discursive and subjective practices found on Web 2.0, as to observe the effects of meanings in the speech of the subject teacher, more specifically on a website whose main focus is to prepare and guide the teacher to qualify himself for teaching and learning using these new technologies. The corpus is compound by e-texts from the educational website Educarede, an Educational Portal sustained by Telefônica and supported by the MEC. We elected to theoretic perspective the French Speech Analysis, the studies by Foucault (2007, 2000, 1991), about speech order and about the “self” technics; and Bauman (1998, 2001, 2005, 2007), Hall (2000); Coracini (2006); Eckert-Hoff (2008) to the matter of new technologies and identity. About education and internet, authors such as Belloni (2005, 2006), Brunner (2003) and Silva (2003). The results indicate an authoritarian, prescriptive and objective speech by the subject teacher. This is a time of changes, and in order to belong to it, the 2.0 subject teacher must not be a human teacher, but he has to link to himself all the Web 2.0 tools which shall make him the Teacher 2.0. This way, the teachers seem to be seen as machines with no self-identity, but with many identifications which can be changed at any moment according to present needs.